Avaliação da participação das células NK (células CD56+) na resposta ao paracoccidioides brasiliensis - Longhi, Larissa Nara Alegrini, 1982- (2010)
Orientadores: Ronei Luciano Mamoni, Maria Heloisa Souza Lima Blotta